Impacts of Tangible and Intangible Asset Investment on Value of Manufacturing Companies Listed on the Indonesia Stock Exchange - Saleh, Mustaruddin (Archives of Business Research, 2018)
ABSTRACT This paper was conducted to examine the effect of tangible and intangible assets investments on the value of manufacturing companies listed on the Indonesia Stock Exchange. 51 of 143 companies were selected using the purposive sampling method with 255 observations during the period 2012-2016. This research uses three regression models for panel data estimation, namely, the common effect model (CEM), fixed effect model (FEM), and random effect model (REM). Measurement of firm value is done using 3 alternative dependent variables, which are: return on asset (ROA), price to book value (PBV), and stock return (Rt). The result of the analysis showed that FEM is more precise in predicting the influence of independent variable to dependent variable, because the probability value of Cho-test and Hausman test is smaller than α = 0.05. The result of data analysis using FEM showed that from the two independent variables used, only the tangible asset variable and the other three control variables, namely, current ratio (CR), earnings per share (EPS), and net profit margin (NPM) have significant effect on firm value. The results of study is in line with previous research (Cao, 2015; Berk, et al., 1999; and Carlson, et al., 2006), which reported that investment in tangible assets negatively affected the short-term return of the company. This supports the fact that the aim of investors in the Indonesian capital market are for profit taking in short-term oriented.